2017
DOI: 10.1073/pnas.1713863114
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor sequencing of early-stage breast cancer tumors identifies altered clonal structure of the T cell repertoire

Abstract: SignificanceThe recent advances in cancer immunotherapy motivated us to investigate the clonal structure of the T cell receptor repertoire in breast tumors, normal breast, and blood in the same individuals. We found quantitatively distinct clonal structures in all three tissues, which enabled us to predict whether tissue is normal or tumor solely by comparing the repertoire of the tissue with blood. T cell receptor sequences shared between patients’ tumors are rare and, in general, do not appear to be specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…Because tumor tissues are removed by surgical excision, the prognostic benefit of CD8 + TRMs likely reflects a greater systemic immunity involving circulating CD8 + T cells with shared antigen specificity or at least tumor specificity with tumor CD8 + TRMs. Although tumor specificity of breast tumor TILs and TRMs has not been formally proved, T cell receptor repertoire analysis of matched patient samples has shown that certain clonotypes are enriched in the tumor and not in NCBT (42,43). TRMs may also develop in peripheral tissues independent of antigen presence because of the presence of various cytokines common in tumor microenvironments, such as TGF-β, TNF-α, IL-33, and IL-15 (44,45).…”
Section: Figure 6 Proximity Of Cd103 + Cd8 + Trms and Not Cd103 − CDmentioning
confidence: 99%
“…Because tumor tissues are removed by surgical excision, the prognostic benefit of CD8 + TRMs likely reflects a greater systemic immunity involving circulating CD8 + T cells with shared antigen specificity or at least tumor specificity with tumor CD8 + TRMs. Although tumor specificity of breast tumor TILs and TRMs has not been formally proved, T cell receptor repertoire analysis of matched patient samples has shown that certain clonotypes are enriched in the tumor and not in NCBT (42,43). TRMs may also develop in peripheral tissues independent of antigen presence because of the presence of various cytokines common in tumor microenvironments, such as TGF-β, TNF-α, IL-33, and IL-15 (44,45).…”
Section: Figure 6 Proximity Of Cd103 + Cd8 + Trms and Not Cd103 − CDmentioning
confidence: 99%
“…All four models were trained using 20 runs of 4-fold cross validation. To evaluate their performances, we applied each model to the treatment-naïve cancer patient cohorts, including melanoma, breast, ovarian, and pancreatic cancers (8)(9)(10)(11). We used the 176 age-matched healthy donors from the Emerson et al, 2017 cohort as control (3).…”
Section: Iv) Cnn With Pca Encodingmentioning
confidence: 99%
“…To learn whether our observations in the mouse model might be relevant to human breast cancer, we compared the mouse TCR data to three, previously published human TCR datasets, each of which focused on a different aspect of breast cancer (Figure 3a) (Beausang et al, 2017;Page et al, 2016;Wang et al, 2017): Beausang et al (Beausang et al, 2017) studied T cell receptors in early-stage breast cancer and sampled the tumor tissue, the surrounding normal tissue and peripheral blood. Wang et al (Wang et al, 2017) sequenced the TCR repertoires of breast cancer tumors, lymph nodes and adjacent tissue.…”
Section: Fig 1 Experimental Procedurementioning
confidence: 99%